2017
DOI: 10.1002/term.2383
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of graft morphology and function after recellularization of decellularized rat livers

Abstract: Decellularization of livers is a well-established procedure. Data on different reseeding techniques or the functional evolution and reorganization processes of repopulated grafts remains limited. A proprietary, customized bioreactor was established to repopulate decellularized rat livers (n = 21) with primary rat hepatocytes (150 × 10 cells) via the hepatic artery and to subsequently evaluate graft morphology and function during 7 days of ex vivo perfusion. Grafts were analysed at 1 h, 6 h, 12 h, 24 h, 3 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Studies investigating whether this approach is feasible are lacking. Several studies have successfully achieved reendothelialization (with or without coating the remaining ECM) and parenchymatous recellularization of liver scaffolds in vitro [8,20,64,73,112,113,[116][117][118][119][120][121][122][123]. Various cell types, such as hepatocytes (e.g.…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating whether this approach is feasible are lacking. Several studies have successfully achieved reendothelialization (with or without coating the remaining ECM) and parenchymatous recellularization of liver scaffolds in vitro [8,20,64,73,112,113,[116][117][118][119][120][121][122][123]. Various cell types, such as hepatocytes (e.g.…”
Section: Livermentioning
confidence: 99%
“…The existing studies have achieved an in vitro cultivation of the neo-livers for up to 28 days and revealed restored functionality (e.g. albumin secretion, urea production, ammonium metabolism and enzyme regulation), drug metabolism and viability of the seeded cells [8,20,64,73,79,81,112,113,[116][117][118][119]121]. According to Robertson et al, recellularized livers produce albumin and metabolize midazolam until the end of their study at 28 days.…”
Section: Livermentioning
confidence: 99%
“…The recellularization of the decellularized tissue should be optimized in order to fabricate a functional reconstructed liver. Previous reports suggested that recellularized liver inoculated with hepatocytes expresses liver-specific functions such as albumin and urea synthesis [5,6]. Also, site-specific cell inoculation has been successfully performed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, allowing liver reconstruction by authentic cell-cell and cell-matrix interactions, which are essential for cell differentiationand maintenance of specialized function. 29 In another study by Butter et al 30 it was suggested, to utilize the repopulated grafts soon after cell engraftment and graft re-organization to avoid loss of functional hepatocytes.…”
Section: Discussionmentioning
confidence: 99%